The Role of Human T-Lymphotropic Virus Type 1 (HTLV-1)-Infected Dendritic Cells in the Development of HTLV-1-Associated Myelopathy/Tropical Spastic Paraparesis - Makino, Masahiko (American Society for Microbiology, 1999)
The development of human T-lymphotropic virus type 1 (HTLV-1)-associated myelopathy/tropical spastic paraparesis (HAM/TSP) is closely associated with the activation of T cells which are HTLV-1 specific but may cross-react with neural antigens (Ags). Immature dendritic cells (DCs), differentiated from normal donor monocytes by using recombinant granulocyte-macrophage colony-stimulating factor and recombinant interleukin-4, were pulsed with HTLV-1 in vitro. The pulsed DCs contained HTLV-1 proviral DNA and expressed HTLV-1 Gag Ag on their surface 6 days after infection. The DCs matured by lipopolysaccharides stimulated autologous CD4(+) T cells and CD8(+) T cells in a viral dose-dependent manner. However, the proliferation level of CD4(+) T cells was five- to sixfold higher than that of CD8(+) T cells. In contrast to virus-infected DCs, DCs pulsed with heat-inactivated virions activated only CD4(+) T cells. To clarify the role of DCs in HAM/TSP development, monocytes from patients were cultured for 4 days in the presence of the cytokines. The expression of CD86 Ag on DCs was higher and that of CD1a Ag was more down-regulated than in DCs generated from normal monocytes. DCs from two of five patients expressed HTLV-1 Gag Ag. Furthermore, both CD4(+) and CD8(+) T cells from the patients were greatly stimulated by contact with autologous DCs pulsed with inactivated viral Ag as well as HTLV-1-infected DCs. These results suggest that DCs are susceptible to HTLV-1 infection and that their cognate interaction with T cells may contribute to the development of HAM/TSP.